Implementation of Street Vendor Arrangement Policy in Wonoasri Village, Tempurejo District, Jember Regency - Ningtyas, Sikta Juniarti; Sunarto, Imam; Asmuni, Asmuni (Jurnal Administrasi Pemerintahan Desa, 2024)
The implementation of the policy of structuring street vendors in Wonoasri village is carried out by providing separate policies for street vendors in Wonoasri village, building public facilities in the village square in order to increase convenience in trading, increase community resources for the village community, reduce unemployment, entertainment and gathering places for the community and increase economic value in selling. These conditions are also influenced by the Bumdes to manage street vendors in the Wonoasri Village square, where the Bumdes plays a role as a policy maker, rent financial regulator, facility provider, provider of rental space for street vendors, and supervisor of harmony between street vendors. One of the objectives of this study is to describe the implementation of the policy of structuring street vendors in the village square of Wonoasri, Jember Regency, which can be seen from three factors, namely the perspective of compliance, success, satisfaction and beneficiaries. This research specifically uses a qualitative approach method, the techniques in data collection used are observation, documentation and interview methods. The results of this study state that the implementation of the street vendor arrangement policy in Wonoasri Village, Tempurejo District, Jember Regency involves the Wonoasri Village Government, Wonoasri Village Bumdes, Street Vendors and the community around the Wonoasri Village Square. So it can be said that this policy has been successful and is a successful implementation. In implementing the policy of arranging street vendors in Wonoasri Village Square, there are several obstacles, including: Controlling the number of new street vendors, the discipline of street vendors and facilities and infrastructure that were previously inadequate but are now well met such as water, electricity, toilets, trash bins, selling space, prayer rooms, and parking lots. Improve better facilities and infrastructure so that traders and visitors can be more comfortable when visiting the Wonoasri Village Square.